2017
DOI: 10.1038/s41598-017-14868-x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc enhances the cellular energy supply to improve cell motility and restore impaired energetic metabolism in a toxic environment induced by OTA

Abstract: Exogenous nutrient elements modulate the energetic metabolism responses that are prerequisites for cellular homeostasis and metabolic physiology. Although zinc is important in oxidative stress and cytoprotection processes, its role in the regulation of energetic metabolism remains largely unknown. In this study, we found that zinc stimulated aspect in cell motility and was essential in restoring the Ochratoxin A (OTA)-induced energetic metabolism damage in HEK293 cells. Moreover, using zinc supplementation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 92 publications
0
19
0
Order By: Relevance
“…(2013) . Studies have shown that the liver lipid metabolism was influenced when rats were given 210 μg/kg body weight OTA ( Qi et al., 2014 ) and decreased the expression of PPARG in human embryonic kidney (HEK) 293 cells treated with OTA ( Yang et al., 2017 ). There was no difference of PPARG expression between CON and OTA groups, which may be due to the animal species and the OTA dosage.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) . Studies have shown that the liver lipid metabolism was influenced when rats were given 210 μg/kg body weight OTA ( Qi et al., 2014 ) and decreased the expression of PPARG in human embryonic kidney (HEK) 293 cells treated with OTA ( Yang et al., 2017 ). There was no difference of PPARG expression between CON and OTA groups, which may be due to the animal species and the OTA dosage.…”
Section: Discussionmentioning
confidence: 99%
“…In isolated brain mitochondria, submicromolar concentrations of zinc can increase oxygen consumption and reduce reactive oxygen species generation, which led Sensi et al 102 to speculate that mitochondrial zinc pools may have a physiological function for the nervous system. Supplementation of media with added zinc in human embryonic kidney HEK‐293 cells can offset impaired cell viability and motility and improve the cellular energy supply disrupted by ochratoxin A toxicity 103 . Zinc uptake by mitochondria is necessary during neuronal differentiation, and ZIP12 may be part of a pathway that can increase cellular zinc uptake to promote mitochondrial zinc influx.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of media with added zinc in human embryonic kidney HEK-293 cells can offset impaired cell viability and motility and improve the cellular energy supply disrupted by ochratoxin A toxicity. 103 Zinc uptake by mitochondria is necessary during neuronal differentiation, and ZIP12 may be part of a pathway that can increase cellular zinc uptake to promote mitochondrial zinc influx. We have previously shown that an increase in Zinpyr-1 fluorescence occurs during Neuro-2a differentiation.…”
Section: Possible Mechanisms For Zinc Influx Through Zinc Transportmentioning
confidence: 99%
“…Furthermore, in a mouse model of AD, dietary zinc supplementation has been shown to restore impaired mitochondrial respiration and also increase levels of brain-derived neurotrophic factor (BDNF), which itself is linked to mitochondrial dynamics and oxidative efficiency [37,[65][66][67]. The importance of zinc for energy metabolism is further supported by the fact that zinc chelation by N,N,N′,N′-tetrakis(2-pyridinylmethyl)-1,2-ethanediamine (TPEN) results in a 50% reduction of ATP production in hepatocytes [68].…”
Section: Introductionmentioning
confidence: 99%